Determinação de resíduos de pesticidas em alimentos por cromatografia a líquido acoplada a analisadores de espectrometria de massas - Chiarello, Marilda (My University, 2019)
Contamination from pesticide residues has become a major concern due to the consequences to living things and the environment. On the other hand, in relation to agribusiness, pesticide residues have become a commercial barrier in the case of exports, for example. Whereas matrices are complex and concentrations of pesticides very low, there is a need for sensitive and selective analytical methods sufficient for the indentification and quantification of these contaminants. Thus, as important as the analytical method, capable of detecting a variety of organic contaminants at the trace level, a good sample preparation procedure is also necessary. Therefore, the present work had the general objective, presented in the form of scientific articles: to address the use of high resolution mass spectrometry (HRMS) for the simultaneous identification and quantification of pesticides. Different matrices and extraction methods were addressed: (i) natural grape juice with analysis and optimization of the QuEChERS method for the preparation of the sample (ARTICLE 1); (ii) present a second quantitative application of the use of QuEChERS and LC-HRMS for different matrices (apple, lettuce and wheat flour) (ARTICLE 2); (iii) optimize and use the QuEChERS method with LC-HRMS for quantification of pesticide residues in organic carrots (ARTICLE 3) and (iv) optimize and use the QuPPe method for the extraction of polar pesticides and metabolites, without derivatization, by low resolution mass spectrometry (LRMS) in olive oil (ARTICLE 4). These procedures address the importance of optimizing sample preparation, QuEChERS and QuPPe, to achieve adequate recovery of pesticide residues in food. In addition, it was sought to minimize the matrix effects caused by the interferents present in the extract. In this way, the use of mass spectrometry associated with separation systems (liquid chromatography) has proved to be an adequate analytical tool for identification and quantification of pesticides in complex matrices. This work demonstrates that the control of contamination of different matrices by organic contaminants, demand adequate sample preparation as well as optimization of the analytical system.
A contaminação por resíduos de pesticidas, têm se tornado uma grande preocupação devido às consequências aos seres vivos e ao ambiente. Por outro lado, em relação ao agronegócio, resíduos de pesticidas têm se tornado barreira comercial no caso de exportações, por exemplo. Visto que, as matrizes são complexas e as concentrações de pesticidas muito baixas, há necessidade de métodos analíticos sensíves e seletivos o suficiente para a identificação e quantificação desses contaminantes. Com isso, tão importante quanto o método analítico, capaz de detectar uma variedade de contaminantes orgânicos em nível de traços, também se faz necessário um bom procedimento de preparo de amostra. Portanto, o presente trabalho teve por objetivo geral, apresentado na forma de artigos científicos, abordar o emprego da espectrometria de massas de alta resolução (EMAR) para a identificação e quantificação simultânea de pesticidas. Diferentes matrizes e métodos de extração foram abordados: (i) suco de uva natural com análise e otimização do método QuEChERS para o preparo da amostra (ARTIGO 1); (ii) apresentar uma segunda aplicação quantitativa do uso de QuEChERS e CL-EMAR para diferentes matrizes (maçã, alface e farinha de trigo (ARTIGO 2); (iii) otimizar e empregar o método QuEChERS com CL-EMAR para quantificação de resíduos de pesticidas em cenouras orgânicas (ARTIGO 3) e (iv) otimizar e empregar o método QuPPe para a extração de pesticidas polares e metabólito, sem derivatização, por espectrometria de massas de baixa resolução (EMBR) em azeite de oliva (ARTIGO 4). Esses procedimentos abordam a importância da otimização do preparo de amostra, QuEChERS e QuPPe, para se obter recuperação adequada de resíduos de pesticidas em alimentos. Além disso, buscou-se a minimização dos efeitos de matriz causados pelos interferentes presentes no extrato. Dessa forma, o uso de espectrometria de massas associado a sistemas de separação (cromatografia a líquido) demonstrou ser uma ferramenta analítica adequada para identificação e quantificação de pesticidas em matrizes complexas. Este trabalho demonstra que o controle de contaminação de matrizes diferentes por contaminantes orgânicos, demanda adequado preparo de amostra, bem como otimização do sistema analítico.
Keywords: Pesticidas; Espectrometria de massa; Alimentos - Contaminação; Pesticides; Mass spectrometry; Food contamination